Discussiedossier: Studiefinanciering en de universiteiten - Knegtmans, P.J.; Schalk, Ruben; Marchand, Wouter; Slaman, Pieter (Studium, 2018)
Discussion paper about three dissertations and a book recently published on the Dutch system of Higher Education financing.